Comparative Post-Yield Performance Evaluation of Flexural Members under Monotonic and Cyclic Loadings based on Experimental Tests. (June 2015) - Dadi, V.V.S. Surya Kumar; Agarwal, Pankaj
Abstract: The non-linear performances of RC beam specimens under flexure are evaluated with constant % of Thermo Mechanically Treated (TMT) reinforcement in confined and unconfined conditions by pushover and cyclic loading. The pushover and cyclic behavior of the beam specimens is plotted in the form of load-deformation for determining the non-linear modeling parameters as per ASCE/SEI 41-06. The beam specimens under cyclic testing have shown large yield strength but low ductility as compared to pushover testing. It may be concluded that the ductility, which is synonymously used without the relevance either of monotonic or cyclic load of a component or a structure, may result to be lethal if appropriation is neglected in behavior factor in seismic design. The confining of transverse reinforcement is another significant parameter on which the post-yield force–deformation relationship and the resulting ductility of an RC component depend. Highlights: Comparison of ductility under pushover and cyclic loading Plastic hinge parameter of flexural member Hysteresis behavior of flexural member under ductile reinforcement Acceptance criteria of flexural member Moment rotation relation under push over and cyclic loading